The Effect of Knowledge Management on Employee Innovation - Sunaryo, Widodo; Santoso, Arief Budi; Moeins, Anoesyrwan (Riviera Publishing, 2022)
This study aims to analyze the effect of Knowledge Management on ASN Employee Innovation of the Ministry of Transportation. The number of samples in this study were 249 respondents using the slovin technique from all units in the Ministry of Transportation. Data was collected using questionnaires, observations and interviews with related parties. The data analysis technique used is the mix method with multiple linear regression analysis and indicator analysis. The results show that the Knowledge management variable partially has a positive effect on Employee Innovation at a significance level of 0.05 with a beta coefficient (?) 0.180 with the resulting regression equation is Y 108.581 0.180X 2 which means that every increase in one level of Knowledge Management will resulted in an increase in Employee Innovation of 0.180 at a constant of 108,581. Thus, knowledge management is predicted to increase employee innovation.